Pain, healing and satisfaction of women after perineal repair with surgical glue and suture - Percela Moscoso Tence Marks; Adriana Caroci-Becker; Wesllanny Sousa Brunelli; Sheyla Guimarães de Oliveira; Marlise de Oliveira Pimentel Lima; Maria Luiza Gonzalez Riesco
Abstract OBJECTIVE To compare the intensity of pain, the healing process and women's satisfaction with the repair of perineal trauma during vaginal delivery using surgical glue or suture. METHOD Cross-sectional study aligned with a clinical trial conducted at a maternity in Itapecerica da Serra, São Paulo. The sample consisted of women who were evaluated between 10 and 20 days after delivery. The outcomes were analyzed according to the distribution of women in the experimental group (EG: perineal repair with Glubran-2® surgical glue; n=55) and in the control group (CG: perineal repair with Vicryl® suture thread; n=55). RESULTS 110 puerperal women were evaluated. There was no difference between EG and CG regarding sociodemographic and clinical-obstetric characteristics. The intensity of perineal pain, assessed by the visual numeric scale was lower among women in the EG compared to the CG (p<0.001). According to the REEDA scale, there was no significant difference in perineal healing (p=0.267) between EG and CG. The satisfaction of women with perineal repair, assessed using a five-point scale, was higher with the use of surgical glue (p=0.035). CONCLUSION Surgical glue showed advantages in relation to perineal pain and greater satisfaction for women compared to the use of suture. The healing process was similar for both types of repair.